Transition properties of the X3Σ–g, A′3Δu, A3Σ+u, B′′3Πu, B3Σ–u, and B′3Πg states of sulphur dimer. (February 2020) - Xing, Wei; Shi, Deheng; Sun, Jinfeng
Highlights: Lifetimes are approximately 10 ns for the B 3 Σ – u state. Lifetimes are in the order of 1 and 10 µs for the B′Πg and B′′Πu states, respectively. Lifetimes are approximately 0.1 – 1 µs for the B′′ 3 Πu, 0+ and B′′ 3 Πu, 1 states. B′ 3 Πg – B′′ 3 Πu and B′ 3 Πg – B 3 Σ – u transitions are weak. B 3 Σ – u –X 3 Σ – g, B′ 3 Πg –A′ 3 Δu, B′ 3 Πg –A 3 Σ + u, and B′′ 3 Πu –X 3 Σ – g transitions are strong. Abstract: In this study, we calculated the properties of the transition between six lowest-lying triplet states (X 3 Σ – g, A′ 3 Δu, A 3 Σ + u, B′′ 3 Πu, B 3 Σ – u, and B′ 3 Πg ) of sulphur dimer. The calculations were made with the CASSCF method, followed by the valence icMRCI approach. It was found that the radiative lifetime of the B 3 Σ – u state is in the order of 10 ns. The Einstein A coefficients of certain vibronic emissions from the B 3 Σ – u – X 3 Σ – g system were large, and the radiative lifetimes of the B′Πg and B′′Πu states were found to be in the order of 1 and 10 µs, respectively. The B′ 3 Πg – A′ 3 Δu, B′ 3 Πg – A 3 Σ + u, and B′′ 3 Πu – X 3 Σ – g transitions were strong and could be measured by spectroscopy. In contrast, the B′ 3 Πg – B′′ 3 Πu and B′ 3 Πg – B 3 Σ – u transitions were weak and therefore, difficult to be detected via spectroscopy. The distributions of the radiative lifetimes with varying rotational angular momentum quantum number were evaluated for some lower vibrational states of the B′′ 3 Πu, B 3 Σ – u, and B′ 3 Πg states. The spin–orbit coupling effect on the transition properties of the B′′Πu – X 3 Σ – g system was also studied. The radiative lifetimes of the B′′ 3 Πu, 0+, B′′ 3 Πu, 1, and B′′ 3 Πu, 2 states were in the order of 10 −6 – 10 −7, 10 −6 – 10 −7, and 10 −5 s, respectively. The transition properties reported in this study can be used to guide the detection of sulphur dimers in both laboratory experiments and astrophysical environments. Graphical Abstract: The transition properties are calculated between the X 3 Σ – g, A′ 3 Δu, A 3 Σ + u, B′′ 3 Πu, B 3 Σ − u, and B′ 3 Πg states of Sulphur dimer. The radiative lifetimes are in the order of 10 ns, 1 µs and 10 µs for the B 3 Σ − u, B′Πg, and B′′Πu states, respectively. The B 3 Σ − u – X 3 Σ − g, B′ 3 Πg – A′ 3 Δu, B′ 3 Πg – A 3 Σ + u, and B′′ 3 Πu – X 3 Σ − g transitions are strong and therefore, easy to measure via spectroscopy. The B′ 3 Πg – B′′ 3 Πu and B′ 3 Πg – B 3 Σ − u transitions are weak and therefore, difficult to detect through spectroscopy. The radiative lifetimes are in the order of 10 −6 – 10 −7, 10 −6 – 10 −7, and 10 −5 s for the B′′ 3 Πu, 0+, B′′ 3 Πu, 1, and B′′ 3 Πu, 2 Ω states, respectively. The B′′ 3 Πu, 0+ – X 3 Σ − g, 0+ and B′′ 3 Πu, 1 – X 3 Σ − g, 1 transitions are strong, whereas the B′′ 3 Πu, 0+ – X 3 Σ − g, 1 and B′′ 3 Πu, 1 – X 3 Σ − g, 0+ transitions are weak. Image, graphical abstract